2021
DOI: 10.1080/13814788.2021.1954154
|View full text |Cite
|
Sign up to set email alerts
|

Psychological outcomes amongst family medicine healthcare professionals during COVID-19 outbreak: A cross-sectional study in Croatia

Abstract: Background Healthcare professionals (HCPs) in family medicine (FM) in Croatia work in a demanding environment caused by the SARS-CoV-2 pandemic. Besides particular circumstances in healthcare, an unknown virus, social distancing, and homeschooling, the capital was hit with the earthquake during the lockdown. Objectives To assess the prevalence of stress, anxiety, depression, posttraumatic stress disorder (PTSD) and the influence of demographic characteristics, professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
(59 reference statements)
1
10
0
2
Order By: Relevance
“…According to it, with the onset of the pandemic, its psychological impact and the development of severe anxiety and distress were determined by several sociodemographic and interpersonal variables including age, fears specific to the pandemic, the quality of relationships within the family, keeping a basic daily routine, change in the economic situation, history of any mental disorder and being afraid that him/herself or a family member will get COVID-19 and die. Similar findings concerning the effects of these factors have been reported in the literature [7,17,32,35,36,46,56,57,65,67,70,80,95,98,107,[111][112][113], Garre-Olmo et al 2021; [89], but until now their detailed contribution had not been identified and no comprehensive model had been Fig. 2 The model which was previously developed in the general population and was proven valid also in the population of health professionals.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…According to it, with the onset of the pandemic, its psychological impact and the development of severe anxiety and distress were determined by several sociodemographic and interpersonal variables including age, fears specific to the pandemic, the quality of relationships within the family, keeping a basic daily routine, change in the economic situation, history of any mental disorder and being afraid that him/herself or a family member will get COVID-19 and die. Similar findings concerning the effects of these factors have been reported in the literature [7,17,32,35,36,46,56,57,65,67,70,80,95,98,107,[111][112][113], Garre-Olmo et al 2021; [89], but until now their detailed contribution had not been identified and no comprehensive model had been Fig. 2 The model which was previously developed in the general population and was proven valid also in the population of health professionals.…”
Section: Discussionsupporting
confidence: 73%
“…Means of responses (from -2 to + 2) to all conspiracy theories by current clinical depression and history of any mental disorder and ANOVA results On the other hand, several factors not assessed by the current study, including the level of training, whether the person worked in the frontline against COVID or in an ICU, etc [8,54,67,111,112],Mira et al 2020;. …”
mentioning
confidence: 75%
“…Unlike prior outbreaks, the COVID-19 pandemic could have a potentially long-term psychological impact on both the general public and HCWs. One year following the start of the pandemic, few studies have been conducted to assess the psychological impact among HCWs using the Depression, Anxiety, and Stress Scale (DASS-21) questionnaire (9)(10)(11)(12)(13)(14)(15). Also, few longitudinal studies have been conducted to evaluate the long-term impact of the pandemic on health care providers (16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…7 En el presente estudio, los médicos familiares mostraron niveles de depresión mínimos en 90.4% y leve en 9.6%, no se reportaron casos de depresión moderada o grave, estos valores se encuentran por debajo de los niveles de depresión reportados en estudios previos, con personal de salud de diversas categorías. 9,10,[12][13][14][15][16] Reportes previos, cuya población de estudio fueron trabajadores de atención primaria en Mascate, 17 internistas y médicos familiares japoneses, 18 así como médicos familiares de Croacia, 19 también reportaron niveles de depresión superiores al presente estudio con 18.1%, 15% y 30.7% respectivamente. Las diferencias en los resultados de los niveles de depresión entre los médicos familiares que participaron en este trabajo y los reportes señalados posiblemente se debieron a que no atendían de manera continua a pacientes sospechosos o confirmados de covid-19.…”
Section: Discussionunclassified
“…10,11 Un estudio italiano reportó, durante uno de los picos de covid-19, que 51.1% de los médicos presentaba depresión, 12 en Irán se reportó un 20.6%, 13 en Etiopía, 16.3%, 14 en Jordania, 19%, 15 en otras partes del mundo esas cifras llegaron hasta 65% en distintos profesionales de la salud. 9,10,[16][17][18][19] Las cifras de depresión y de otras enfermedades mentales ha sido una constante durante la pandemia de covid-19 para muchos profesionales de la salud, incluidos médicos familiares de diversas partes del mundo, [20][21][22] esto ha impactado de manera notoria en la satisfacción laboral debido a que en múltiples escenarios la carga de trabajo fue mayor para el personal de salud que atendía pacientes con covid-19. [23][24][25][26][27][28] Una vez analizado ese contexto, el objetivo del presente trabajo fue identificar la sintomatología depresiva y la satisfacción laboral en médicos familiares de la unidad de medicina familiar (umf ) No.…”
Section: Introductionunclassified